Cervical cancer screening with HPV testing in the Valcamonica (Italy) screening programme. (March 2015) - Pasquale, L; Giorgi Rossi, Paolo; Carozzi, F; Pedretti, C; Ruggeri, C; Scalvinoni, V; Cotti Cottini, M; Tosini, A; Morana, C; Chiaramonte, M; Sacristani, MF; Cirelli, R; et al.
Objective: We present the results of the first screening round and the first year of the second round of the Valcamonica Human Papillomavirus (HPV) pilot screening project. Setting: From 2010 to 2012, the entire target female population (aged 25–64) was invited to the first HPV screening round in an area where Pap test screening had been active since 2002. Methods: For HPV-negative women, the interval was three years. For HPV-positive women, a cytological smear was stained and interpreted. Positive cytologies were referred to colposcopy; negatives were referred to repeat HPV after one year. If HPV was persistently positive, women were referred to colposcopy; if negative, to normal screening. Results: In 2010–12 18728 women were screened, slightly higher participation than with Pap test (18233 64.7%); 1633 were HPV-positive (8.7%); 843 were positive at cytology triage (referral rate at baseline 4.5%). Of those referred at the one year HPV test, 84% complied (660/780); 356 were persistently positive (1.9%). The total referral rate was 6.4% compared with 3.7% for the Pap test. The detection rate was 9.2/1000 compared with 5.0% for the Pap test. The HPV positivity rate during the second round in women previously negative was 3.9% and the detection rate in HPV-positive cytology-positive women was 0.8/1000. Conclusions: HPV-based screening increases colposcopies at the first round, but also strongly increases the detection rate. At the second round, HPV prevalence was much lower and the detection rate also fell, corroborating the need for longer screening intervals in HPV-negative women.